Interfaith Interaction in Gen Z Friendship Circles from a Multicultural Communication Perspective - Alya Tandiva Azzahra; Poppi Damayanti (Yayasan Darussalam Bengkulu, 2025)
Interfaith interaction within the friendship circle of Generation Z (Gen Z) is an interesting phenomenon. This study aims to explore how interfaith friendships influence the formation of an inclusive and tolerant social identity. This study used a descriptive qualitative research method with interviews involving Gen Z respondents who experienced interfaith interaction, especially within the friendship circle. The results show how social media plays a significant role in creating inclusive discussion spaces. Gen Z demonstrates a high level of multicultural awareness in terms of acceptance and appreciation of religious differences, although challenges in the form of initial prejudice and limited knowledge remain. The experience of interfaith friendships has been shown to foster the formation of a more open, inclusive, and empathetic character.